2011
DOI: 10.1371/journal.pone.0025415
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Hemodynamic Oscillations during Human Sleep and Sleep Stage Transitions Characterized with Near-Infrared Spectroscopy

Abstract: Understanding the interaction between the nervous system and cerebral vasculature is fundamental to forming a complete picture of the neurophysiology of sleep and its role in maintaining physiological homeostasis. However, the intrinsic hemodynamics of slow-wave sleep (SWS) are still poorly known. We carried out 30 all-night sleep measurements with combined near-infrared spectroscopy (NIRS) and polysomnography to investigate spontaneous hemodynamic behavior in SWS compared to light (LS) and rapid-eye-movement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 61 publications
7
43
0
Order By: Relevance
“…The mean change in tHb was 1.02 ± 6.81 µM (p=0.704, n=7), which was not significant. Individual data are shown 4 in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean change in tHb was 1.02 ± 6.81 µM (p=0.704, n=7), which was not significant. Individual data are shown 4 in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…While different studies investigated specific events during sleep, e.g. sleep apnoea [3], differences between sleep stages [4] or wakefulness and sleep [5] the temporal evolution of 2 the oxygen metabolism in the course of sleep is not clear. According to the synaptic homeostasis hypothesis [1], a popular hypothesis about the function of sleep, oxygen demand should be reduced during sleep and hence brain metabolism should be decreased.…”
Section: Introductionmentioning
confidence: 99%
“…amplitude, frequency, phase) can be modulated by the stimulus/task to some degree. For example, it was shown that the amplitude of LF and VLF oscillations depend on the activity state (rest vs. task) (Obrig et al, 2000a), sleep stage (Näsi et al, 2011), body posture (Tachtsidis et al, 2003(Tachtsidis et al, , 2004, or age of the subject (Peng et al, 2008;Safonova et al, 2004). Thus, although these oscillations arise spontaneously, their stimulus/task-evoked modulation capability leads to the conclusion that they may also be part of the systemic activity type 1 and type 2 (SC2-3).…”
Section: Classification Of Signal Componentsmentioning
confidence: 99%
“…In brain hemodynamic imaging, the information is either provided topographically with the information effectively being averaged over the penetration depth of the light, 3,17,[19][20][21][22][23][24] or tomographically exploiting the penetration of visible and/or near-infrared light to provide volumetric information up to a few millimeters or centimeters underneath the surface. 14,[25][26][27][28] Most tomographic approaches are implemented through-skull and lead to diffused functional cortex maps, whereas topographic approaches are most often used for intraoperative applications during open-cranium surgery with brain tissue being imaged without the need to correct for light attenuation caused by intervening tissue including skin and skull.…”
Section: Introductionmentioning
confidence: 99%